Factors predicting future ACS episodes in children with sickle cell anemia. Issue 11 (27th August 2014) - DeBaun, Michael R.; Rodeghier, Mark; Cohen, Robyn; Kirkham, Fenella J.; Rosen, Carol L.; Roberts, Irene; Cooper, Ben; Stocks, Janet; Wilkey, Olu; Inusa, Baba; Warner, John O.; Strunk, Robert C.
<x xml:space="preserve">Abstract</x> While a doctor‐diagnosis of asthma is associated with an increased risk of pain and acute chest syndrome (ACS) in children with sickle cell anemia (SCA), little is known about the relationship between specific asthma characteristics and clinical factors and future morbidity in children with SCA. We evaluated the relationship between (i) asthma risk factors at the time of a clinical visit (respiratory symptoms, maternal history of asthma, allergy skin tests, spirometry results) and (ii) the known risk factor of ACS early in life, on prospective pain and ACS episodes in a cohort of 159 children with SCA followed from birth to a median of 14.7 years. An ACS episode prior to 4 years of age, (incidence rate ratio [IRR] = 2.84; P < 0.001], female gender (IRR = 1.80; P = 0.009), and wheezing causing shortness of breath (IRR = 1.68; P = 0.042) were associated with future ACS rates. We subsequently added spirometry results (obstruction defined as FEV1/FVC less than the lower limits of normal; and bronchodilator response, FEV1 ≥ 12%) and prick skin test responses to the model. Only ≥ 2 positive skin tests had a significant effect (IRR 1.87; P = 0.01). Thus, early in life ACS events, wheezing causing shortness of breath, and ≥ 2 positive skin tests predict future ACS events. Am. J. Hematol. 89:E212–E217, 2014. © 2014 Wiley Periodicals, Inc.